Human Disease/Clinical Medical Sciences in Dentistry: Current state and future directions of undergraduate teaching in the UK and Ireland. (18th April 2018) - Atkin, P. A.; Thomas, S.; Cook, R. J.; Greenwood, M.; Bennett, J. H.; Willis, A.; Donachie, C.; Ni Riordain, R.; Galvin, S.; Crighton, A.; Mighell, A. J.; Bakri, I.
Abstract: In March 2017, a group of teachers of human disease/clinical medical science (HD/CMSD) representing the majority of schools from around the UK and Republic of Ireland met to discuss the current state of teaching of human disease and also to discuss how the delivery of this theme might evolve to inform improved healthcare. This study outlines how the original teaching in medicine and surgery to dental undergraduate students has developed into the theme of HD/CMSD reflecting changing needs as well as guidance from the regulators, and how different dental schools have developed their approaches to reach their current state. Each school was also asked to share a strengths, weakness, opportunities and threats (SWOT) analysis of their programme and to outline how they thought their HD/CMSD programme may develop. The school representatives who coordinate the delivery and assessment of HD/CMSD in the undergraduate curriculum have extensive insight in this area and are well‐placed to shape the HD/CMSD development for the future.